PERENCANAAN PENGAJARAN BAHASA - ROSTINA . (JURNAL ILMIAH MAKSITEK, 2022)
Teaching planning is one of the teaching and learning activities that needs to be done as a first step for submission training, without good planning the purpose of the submission will not be carried out to arrange material acceptance properly for educators because they have pedagogic, personality, professional and social competencies as well as understanding of several Relevant disciplines are linguistics, which include descriptive linguistics, psycholinguistics, sociolinguistics as well as material and pedagogic learning theory. The development of linguistics/linguistics always has an influence on language teaching, and the results of linguistic studies in general can be used as a theoretical basis in teaching planning.